Backmatter (Acknowledgement, author guidelines, back cover) - Mohammad Rofiuddin (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
Backmatter of Indonesian Journal of Islamic Economics Research Vol 2 No 2, 2020